Analisis Pengaruh Motivasi, Disiplin, dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Puskesmas Waplauw - Hans Sammy Marthin Salakory; Febby Sonya Matulessy; Natasya Lopuhaa (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2024)
The quality of health services at the Waplauw Health Center is highly dependent on the optimal performance of its employees. Performance depends on various factors, including motivation, discipline, and work environment. The reality shows that some employees feel that their financial compensation needs to be increased, employees are often late for work, and there is a lack of supporting facilities, all three of which impact employee performance. This study aims to determine the effect of motivation, discipline, and work environment on employee performance at the Waplauw Health Center. The research method used is quantitative with a survey approach. The research sample was 56 employees of Waplauw Health Center—data collection using questionnaires tested for validity and reliability and data analysis using multiple linear regression. The results showed that motivation, discipline, and environment significantly affected employee performance. The work environment has the most dominant effect. The implication of this research for management is to increase employees' intrinsic motivation through various self-development programs, giving appropriate awards, and creating a conducive and supportive work environment.